-5+6m=5m-8

Simple and best practice solution for -5+6m=5m-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5+6m=5m-8 equation:


Simplifying
-5 + 6m = 5m + -8

Reorder the terms:
-5 + 6m = -8 + 5m

Solving
-5 + 6m = -8 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.
-5 + 6m + -5m = -8 + 5m + -5m

Combine like terms: 6m + -5m = 1m
-5 + 1m = -8 + 5m + -5m

Combine like terms: 5m + -5m = 0
-5 + 1m = -8 + 0
-5 + 1m = -8

Add '5' to each side of the equation.
-5 + 5 + 1m = -8 + 5

Combine like terms: -5 + 5 = 0
0 + 1m = -8 + 5
1m = -8 + 5

Combine like terms: -8 + 5 = -3
1m = -3

Divide each side by '1'.
m = -3

Simplifying
m = -3

See similar equations:

| t=2t-51 | | 3y=-x-2 | | 4y-5x=4y-5x | | 8/9-5/6×1/3 | | 4b+64=2b+68 | | 8n-n=-4+6n | | 7c-77=4c-35 | | -4x+4=11+2x-7x | | 9x+16y=7 | | 2/y-3=3/y | | 3q+6=6q | | 3+3(2-6)= | | -5+6x=x+10 | | 2s-48=s | | 2s+40=4s+28 | | x/3-=11 | | 3y=7x-9 | | 9x-12y+6=0 | | 3s-62=s | | 5p-60=p-4 | | n-8-1=-13 | | -5-7k+8k=0 | | x=2x-70 | | -12a-5b=27 | | 3z=z+26 | | r/320 | | 4n-2n+4=1+17 | | 4v-3+8=13 | | -1/2w-7/5=4/3 | | 3+3(2-6)squared= | | -8a-2a=-10 | | b+4=2b-3 |

Equations solver categories